RITUAL AND TRADITIONAL SLAUGHTER PRACTICES FOR MEAT PRODUCTION - Zeiad Amjad Abdulrazzak Aghwan (Journal of Islamic, Social, Economics and Development, 2019)
Undoubtedly, meat is an important source of nutrients that are essential for human health. Slaughtering process plays an important role related to animal welfare, meat quality, safety and public health throughout meat production chain. This paper sets out to present the relevant aspects of ritual and traditional slaughter with recommended animal welfare to reduce pain and maintain meat quality. The procedures used for animal slaughter have varied between regions and faiths. Due to increasing of population size and buying power, the global meat market has become increasingly interested in Islamic halal and Jewish kosher slaughter in particular. Religious slaughter such as halal and kosher compared with other procedures of slaughter remains an argumentative matter among religious groups, welfare groups, scientists, the general public, and governments. The permissibility of pre-slaughter stunning is a central issue separating these religiously-based procedures of animal slaughter from those used by industrial meat producers that have become conventional in developed countries. It is important to optimize efficient bleeding and skilful handling of animals to reduce pain and put wholesome meat on the table of consumers.